Legal Difficulties Associated With the Use of Big Data in Healthcare: Civil Law and Cyberlaw Review - Imamalieva, Diyora (Medicine, Law & Society, 2024)
Current trends suggest a future in which big data can be used to predict individual health risks and outcomes with exceptional accuracy. By analyzing large datasets that include various health indicators, algorithms can predict the onset of disease, allowing for early intervention and personalized treatment plans. However, the legal and ethical implications of predictive health analytics, such as potential misuse of predictive information or unfair discrimination based on health risks, require careful consideration. In terms of global health surveillance, the COVID-19 pandemic has highlighted the potential of big data to track the spread of disease and inform public health responses.